(untitled) (World Bulletin of Social Sciences, 2021)
This article analyzes the issues of educating students in the spirit of national pride. It was noted that the education of students reflects the feelings of national pride and honor, educating them in the spirit of devotion to the motherland is important in the realization of the age-old dreams of our people. In the essence of cultivating feelings of national pride and honor, information is given about the national culture of a certain nation, national traditions and customs, certain periods of people’s lives, psyche, philosophy, which have a great educational impact. Patriotism and national pride are based on the analysis of a person’s deep respect for his family, the honor of his ancestors, conscience, duty and loyalty to his word.